Steve Jobs e o discurso religioso-midiático da Apple - Santos, Amanda Moura da Silva dos (2017)
Steve Jobs’ speech, that marked the launch of products made by Apple, a technology company, was eagerly anticipated by the market, fans and media. All over the world, many people line up and even set up tents in front of Apple stores on the eve of product launches, and then come out holding their package as a trophy. But what explains Apple’s phenomenon? This study is based on the assumption that Jobs is considered a sort of modern times messiah, making Apple an extension of himself, and aims to understand, within an enunciative-discursive perspective, as developed by Dominique Maingueneau, how the messiah figure is personified in Jobs and unveils a “savior” myth established around him. This investigation is also founded on the hypothesis of sacralization of technology (Noble, 1997), which considers that, by promoting the encounter between the physical and the metaphysical, technology aims at transcendence and appropriates religious ideas. As such, this study is spread across different discursive fields, such as advertising, religion and the media, aiming to understand not only the intertextuality but also the discursive ethos and set design in the conjuncture of the public appearances of Apple’s co-founder. In addition, in order to understand how Steve Jobs’ discourse got acclaimed by the world, using the religious discourse to legitimize his own speech, the notion of constituent discourses is thus mobilized. Considering the evolution in the networks of discourse genres, especially after the emergence of the internet and the widespread dissemination of technology, the study also contemplates the notion of generic valence (Maingueneau, 2015), which allows us to reflect on how discourse genres and consequently the exercise of the discourse have been transforming over time. This reflection is essential, since the analysis of this research focuses on events that happened empirically and were reproduced on YouTube, an online video sharing platform. The results show how the pre-discursive ethos was constructed with an interaction between different genres, the discursive artifices used by the enunciator in the scenography of his presentations to challenge his co-exponents, as well as the links between what Jobs demonstrated and the contents circulating about him, raising expectations of his public appearances